2020
DOI: 10.1007/s10336-019-01741-z
|View full text |Cite
|
Sign up to set email alerts
|

Feather corticosterone in Northern Bald Ibis Geronticus eremita: a stable matrix over time able to predict reproductive success

Abstract: Measuring corticosterone concentrations in feathers (FCC) has been increasingly used as an integrated index of bird's response to stressors, offering valuable insights into subsequent carry-over effects. However, it is still unclear to what extent corticosterone levels deposited in feathers during the moulting period relate to individual physiology in high-energetic demanding situations. In addition, the stability and repeatability of FCC over the same feather generation and across successive generations are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…The results of this study also reveal non-significant associations between CORTf, life parameters, and behavior. The finding that the pelicans’ sex did not affect CORTf is comparable to the findings of other studies such as those in northern bald ibises ( Geronticus eremita ) [ 32 ]. The age of the pelicans seems to affect CORTf.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study also reveal non-significant associations between CORTf, life parameters, and behavior. The finding that the pelicans’ sex did not affect CORTf is comparable to the findings of other studies such as those in northern bald ibises ( Geronticus eremita ) [ 32 ]. The age of the pelicans seems to affect CORTf.…”
Section: Discussionsupporting
confidence: 89%
“…(2017) , it is recommended to use the same type of feather when analyzing and comparing feather corticosterone concentrations as the feathers have the same structure and time of growth. When drawing comparisons, feathers should origin from the same replacement generation as Monclús et al. (2020) found different levels of feather corticosterone in the same bird but from different seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies on corticosterone in feathers were performed mostly in wild birds (e.g., Bortolotti et al., 2009 ; Koren et al., 2011 ; Lattin et al., 2011 ; Fairhurst et al., 2012 ; Lendvai et al., 2013 ; Harms et al., 2015 ; Kouwenberg et al., 2016 ; Aharon-Rotman et al., 2017 ; Freeman and Newman, 2018 ; Monclús et al., 2020 ), using feather corticosterone as a retrospective view on challenges the birds had to cope with during feather growth. Despite the wild birds, results of first investigations in poultry ( Berkvens, 2012 ; Carbajal et al., 2014 ; Jenni-Eiermann et al., 2015 ; Zeinstra et al., 2015 ; Johns et al., 2017 ; Weimer et al., 2018 ; Alba et al., 2019 ; von Eugen et al., 2019 ; Nordquist et al., 2020 ; Lindenwald and Rautenschlein, unpublished data) are also encouraging; however, in the absence of a standardized procedure, authors applied different methods to detect and quantify corticosterone in feathers.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of feather corticosterone concentration ( fCORT ) is a comparatively new and increasingly used method in stress research in wild and captive birds as well as in poultry ( Carbajal et al, 2014 ; Romero and Fairhurst, 2016 ; Häffelin et al, 2020 ; Leishman et al, 2020 ; Monclús et al, 2020 ; Reese et al, 2020 ). Numerous studies have reported a stable incorporation of corticosterone in feathers and a positive correlation between corticosterone concentrations in feathers and in peripheral blood ( Bortolotti et al, 2008 ; Romero and Fairhurst, 2016 ).…”
Section: Introductionmentioning
confidence: 99%